Prognostic Factors in Gastrointestinal Stromal Tumors: Multicenter Experience of 333 Cases from Turkey - DANE, FAYSAL (H G E UPDATE MEDICAL PUBLISHING S A, 2013)
Background/Aims: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasm of the gastrointestinal tract. In an attempt to survey the approximate incidence, clinicopathological characteristics, and immunophenotypic features of GISTs in Turkey, we conducted a clinicopathological and immunohistochemical analysis of GISTs. Methodology: Three hundred and thirty-three patients with GIST from nine institutions in Turkey were retrospectively evaluated. Results: Between January 2001 and March 2011, a total of 333 patients with GISTs were included; of these, 204 (61.2%) were male and 129 (38.8%) were female. The median age was 55 years (range; 22402 years). At the median follow-up of 26 months (range; 4-166 months), the 1-, 3- and 5-year OS rates of the 333 patients were 96.9%, 85.8% and 78.5%, respectively. The 5-year DFS rate was 40%. The 5-year OS rate and median OS time for the patients with R-0 resection were significantly higher than for patients with metastatic diseases (79.7 vs. 75.7% and not reached vs. 115 months, respectively, p=0.04). Conclusion: Although our results should be confirmed by prospective studies, we believe that they contribute to the literature because the study included both resectable and metastatic or unresectable GIST patients and multicenter findings from Turkey.
Keywords: Gastrointestinal stromal tumors; Prognosis; Turkey; TERM-FOLLOW-UP; IMATINIB MESYLATE; DIFFERENTIAL-DIAGNOSIS; DOSE IMATINIB; TRIAL; MANAGEMENT; SURVIVAL